Pemilihan Bahan Restorasi yang Tepat untuk Mouth-Preparation Pasien Celah Bibir dan Langit-Langit - Stephanie Stephanie; Eriska Riyanti (Jurnal Material Kedokteran Gigi, 2015)
Children’s dental caries is a dental and oral health problem in Indonesia. Children at school age have high caries risk. Patients with cleft lip and or palate have caries experience similar to normal children. It takes a preventive and curative treatment for patients and their families. The purpose of this case report is to open horizons for the use of restoration in patients with cleft lip and palate, as a form of mouth preparation prior to reconstruction and rhinoplasty surgery. A 10 years- old boy was came with his parents to the Cleft Lip and Palate Foundation, with complaint of his nose form after the cleft lip and palate closure surgery when he was a baby and wanted teeth alignment to be fixed. Clinical examination found dental caries at 55, 54, 53, 63, 64, 74, 84, and 85. Dental treatments proposed included OHI, caries risk assessment, plaque control, dietary analysis, restoration, root canal treatment, and topical fluoride application. Dental care is required in patients who have had cleft lip and palate closure surgery before reconstructive and rhinoplasty surgery. Good oral hygiene will support the success of reconstructive and rhinoplasty surgery.